Impact of Patient-Reported Allergies on Early Postoperative Opioid Use and Outcomes Following Ambulatory Hand Surgery. (March 2022) - Coxe, Francesca R.; Wessel, Lauren E.; Verret, Claire I.; Stepan, Jeffrey G.; Nguyen, Joseph T.; Fufa, Duretti T.
Background: Patient-reported allergies (PRAs) are associated with suboptimal orthopaedic surgery outcomes and may serve as a proxy for mental health. While mental health disorders are known risk factors for increased opioid use, less is known about how PRAs impact opioid use after orthopedic surgery. The purpose of this study was to investigate the association between PRAs and postoperative opioid use, pain, and satisfaction following hand surgery.Methods: Patients who underwent ambulatory hand surgery at a single institution from May 2017 to March 2019 were retrospectively reviewed. Various scores, including the Mindfulness Attention Awareness Scale (MAAS), were collected preoperatively. Postoperatively, patients completed a 2-week pain diary, satisfaction, and visual analog scale (VAS) pain scores. Opioid consumption was converted to oral morphine equivalents (OMEs) using standard conversions.Results: A total of 137 patients were divided into 2 groups based on presence (≥1) (n = 73) or absence (0) (n = 64) of PRAs. At baseline, the ≥ 1 PRA group had significantly higher female composition ( P < .001) and pain ( P < .001) and lower PROMIS mental health scores ( P = .044). Postoperative OME consumption averaged 42.5 (range 0-416) in the entire cohort, with no differences between groups. Among patients with ≥ 1 PRA, increasing number of allergies significantly correlated with increasing OME consumption across all time points (week 1, P = .016; week 2, P = .001; total, P = .005).Conclusions: The presence of PRAs did not impact postoperative narcotic usage, pain, or satisfaction. Increasing numbers of PRAs did, however, significantly correlate with higher narcotic use. These results may have implications for postoperative pain management in this population.